Household Vegetable Gardening in Quezon City, Philippines: Practices, Benefits, and Constraints - Lagdameo, John Luis D.; Dejaresco, Angelica Nicolette B.; Gonzalez, Ma. Cecilia M.; Ignowski, Liz; Schreinemachers, Pepijn; Bertuso, Arma R. (CGIAR System Organization, 2024)
The study collected a wide range of information from respondents. It included details about their identities, such as names, ages, and genders. Additionally, it examined household characteristics, including house size, sources of income, and the number of floors in their homes. The research also explored urban food production and planting practices, identifying the types of vegetables grown, the locations of these planting activities, and the technologies used. Moreover, it investigated food acquisition and meal preparation, focusing on sources of food, safety concerns, and the challenges faced in obtaining these items. Diet diversity was assessed through a one-month recall of food, fruits, and vegetables, where respondents were asked whether they had consumed these items in the past month, how frequently they consumed them, and the approximate quantities. Diet quality was evaluated using a 24-hour recall, detailing the types of vegetables, meat products, and desserts consumed in the last 24 hours. Finally, the study examined food insecurity experiences over a one-month period, noting the preferred foods that respondents were unable to eat due to a lack of resources, the frequency of going to bed hungry, and the reduction in the number of meals consumed per day due to resource constraints.